2016
DOI: 10.1007/s10853-016-0439-x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced polarity and improved dispersion of microfibrillated cellulose in poly(lactic-acid) provided by residual lignin and hemicellulose

Abstract: The surface chemistry and dispersion in poly(lactic-acid) of microfibrillated wood and microfibrillated lignocellulose prepared from untreated and partially delignified beech were compared with conventional microfibrillated cellulose produced from bleached pulp. High heterogeneity in fibril morphology and bulk chemical composition was observed. Also surface chemistry of the fibrils was highly variable, but not clearly correlated with bulk chemistry. Composite solution-cast films of poly(lacticacid) reinforced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 36 publications
(38 reference statements)
2
26
0
Order By: Relevance
“…It is suggested that this denser and less porous structure of MFLC specimens is caused by the wetting and infiltration of cellulose fibrils by FA, providing a significant reinforcement effect upon in situ polymerisation. Considering the furanic ring structure present in FA, wetting of lignin-containing microfibrillated cellulose, which was shown to provide considerably improved miscibility with non-polar solvents and polymers compared to MFC produced from bleached pulp (Ballner et al 2016;Herzele et al 2016;Winter et al 2017;Yan et al 2016), seems highly plausible for furfuryl alcohol. Apart from better wetting and interpenetration, the FA monomer may also directly react with lignin units found in MFLC according to reaction 2 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is suggested that this denser and less porous structure of MFLC specimens is caused by the wetting and infiltration of cellulose fibrils by FA, providing a significant reinforcement effect upon in situ polymerisation. Considering the furanic ring structure present in FA, wetting of lignin-containing microfibrillated cellulose, which was shown to provide considerably improved miscibility with non-polar solvents and polymers compared to MFC produced from bleached pulp (Ballner et al 2016;Herzele et al 2016;Winter et al 2017;Yan et al 2016), seems highly plausible for furfuryl alcohol. Apart from better wetting and interpenetration, the FA monomer may also directly react with lignin units found in MFLC according to reaction 2 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For the preparation of porous materials, two types of microfibrillated cellulose were used, which are both described in more detail elsewhere (Winter et al 2017). Briefly, microfibrillated cellulose produced by mechanical refining of bleached softwood kraft pulp, termed MFC, was purchased from the University of Maine.…”
Section: Preparation Of Porous Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach can also advance the discovery of novel applications without the need for the surface chemical functionalization of the nanofibers (Habibi 2014), leading to a reduction in environmental stress and costs in the production process. Above all, the conservation of lignin is of interest because it increases the hydrophobicity of the nanofibers, which could increase their use in multiple applications, for example, flotation (Laitinen et al 2016), oil-water stabilization (Visanko et al 2014a;Ojala et al 2016), and biocomposites (Herzele et al 2016;Winter et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…2 However, preliminary studies have indicated that the fabrication of nanocellulose from lignin-containing pulps is a cumbersome process, 3 and delignification has been required. 4 Recently, heat-intensified disc nanogrinding of mechanical pulp was introduced to produce wood nanofibers (WNFs). 5 In addition, acid hydrolysis of lignin-containing pulp has been shown to be an efficient way to produce both CNCs and CNFs.…”
Section: Introductionmentioning
confidence: 99%